Análisis y valoración de la arquitectura tradicional de la comunidad de Guzo - Bravo Borja, Santiago Israel (2024)
The traditional architecture of the community of Guzo in the Penipe Canton of the province of Chimborazo, recognized in 1938 as part of the parish of Penipe with an area of 438.12ha, at an altitude of 2430m. m has a cold climate with a temperature of 15°C. This architecture, with its native characteristics, customs, and essential features, is a testament to the richness of Guzo's traditions and architecture. However, it is under threat from globalization and the rapid pace of contemporary architecture that is absorbing these unique qualities and technology, leading to a loss of cultural identity. The lack of studies and knowledge of its inhabitants has allowed the devaluation of this type of architecture, undervaluing the importance of the traditional, where forms, spaces, and construction techniques have been relegated despite being the perfect and unique solution to each site. The objective of this research work is to value the traditional architecture of the community of Guzo in the Penipe Canton through the architectural and constructive technological analysis of the existing buildings that have characteristics of the area to know the unique peculiarities of this community, its current state and the value it brings to its environment, laying a foundation to preserve this traditional cultural identity that exists in Guzo. A methodology with a qualitative and quantitative approach was used for the analysis and valuation of the architectural line of the community, which combines documentary research, architectural analysis, and fieldwork. According to the study carried out, it is concluded that the architecture of Guzo is typical of the area and different from the others because its forms and functions respond to the place and are integrated with its environment; all its spaces have a modulation that allows a relationship with the exterior and its circulations are direct relating to each other, its construction technology is the Bahareque which differs from the traditional one because it is built with wood and not with cane which gives it an autochthonous value that should be preserved.